Genetic polymorphism of hepatitis C virus and risk of hepatocellular carcinoma - S. N. Mammayev; A. M. Karimova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
The aim of review. To estimate effect of genetic polymorphism of hepatitis C virus on risk of hepatocellular carcinomas (HCC).Key points. Hepatocellular carcinoma is one of the most dreadful outcomes of chronic liver diseases, in particular — chronic hepatitis C (CHC). Now it is revealed, that frequency of HCC in patients with 1b genotype of hepatitis C virus (HCV) was significantly above, than other genotypes. In aminoacidic sequences analysis in patients with 1b genotype of HCV mutations with substitution of arginine to glycine in codon 70 (Glu 70) and leucine to methionine in codon 91 (Met 91) were revealed. Thus it is revealed, that mutant type Glu 70 is significantly more frequent in patients with HCC in comparison to CHC and liver cirrhosis, in older age groups, at elevation of serum level of gamma-glutamyltranspeptidase and aspartate aminotransferase. Frequency of mutant forms of 1b genotype is related to discovery of previously unknown protein of HCV — minicor-protein with absence of N-terminal of classical Cor-protein p21.Conclusion. Early detection mutant Glu 70, Met 91 forms of HCV genotype 1b will provide prediction of HCC risk in CHC patients and to begin adequate etiological treatment for preventive maintenance of this dangerous complication intime.